Noninfectious Foodborne Exposures Reported to 2 National Reporting Systems, United States, 2000-2010. (September 2019) - Law, Royal Kai Yee; Kisselburgh, Hannah; Roblin, Douglas; Choudhary, Ekta; Schier, Joshua; Fraser, Michael; Taylor, Ethel
Objectives: Foodborne disease is a pervasive problem caused by consuming food or drink contaminated by infectious or noninfectious agents. The 55 US poison centers receive telephone calls for advice on foodborne disease cases that may be related to a foodborne disease outbreak (FBDO). Our objective was to assess whether poison center call records uploaded to the National Poison Data System (NPDS) can be used for surveillance of noninfectious FBDOs in the United States. Methods: We matched NPDS records on noninfectious FBDO agents in the United States with records in the Foodborne Disease Outbreak Surveillance System (FDOSS) for 2000-2010. We conducted multivariable logistic regression analysis comparing NPDS matched and unmatched records to assess features of NPDS records that may indicate a confirmed noninfectious FBDO. Results: During 2000-2010, FDOSS recorded 491 noninfectious FBDOs of known etiology and NPDS recorded 8773 calls for noninfectious foodborne disease exposures. Of 8773 NPDS calls, 469 (5.3%) were matched to a noninfectious FBDO reported to FDOSS. Multivariable logistic regression indicated severity of medical outcome, whether the call was made by a health care professional, and etiology as significant predictors of NPDS records matching an FDOSS noninfectious FBDO. Conclusions: NPDS may complement existing surveillance systems and response activities by providing timely information about single cases of foodborne diseases or about a known or emerging FBDO. Prioritizing NPDS records by certain call features could help guide public health departments in the types of noninfectious foodborne records that most warrant public health follow-up.